Maxillofacial fibrous dysplasia: a diagnostic challenge. (29th June 2016) - Markov, Peter; Syed, Ali Zakir; Markova, Christiana; Mendes, Rui Amaral
Abstract : A 30-year-old woman presented for orthodontic treatment, with a chief symptom of a 'shifting bite' and concurrent facial asymmetry with aesthetic concerns. The patient had previously received treatment from several general dentists and several specialists, without accurate diagnosis. Radiological investigation coupled with biopsy confirmed a diagnosis of fibrous dysplasia. Proper diagnosis led to changes in the treatment plan and gave the patient realistic expectations about the options she had for the outcome of treatment. Prompt diagnosis by dental practitioners is critical to patient satisfaction and successful outcome; therefore, it is important to familiarise ourselves with the signs, symptoms and proper course of management of fibrous dysplasia.